Analysis Of Environmental, Social, And Governance (Esg) Program Implementation On Corporate Reputation In The Mining Industry - Kristi, Henrika; Arief, Nurlaela (Jurnal Locus Penelitian dan Pengabdian, 2025)
This research employs a mixed methods approach to assess ESG program implementation at PT X, using qualitative analyses of documents, policies, and interviews with stakeholders, including management, employees, and community representatives. The study evaluates the impact of ESG on corporate reputation through both qualitative data, such as media analysis and stakeholder perceptions, and quantitative data that examines correlations between ESG performance indicators and reputation measures like media sentiment and investor confidence. The core assumption is that a well-communicated ESG program enhances a mining company's reputation. The study aims to analyze PT X's current ESG implementation, identifying strengths and challenges, while also determining its impact on corporate reputation across various stakeholder groups. Additionally, it seeks to suggest improvements to PT X's ESG strategy. Existing literature links ESG performance to corporate reputation and financial success, emphasizing transparency and stakeholder engagement. However, specific studies on ESG in the Indonesian mining sector are limited. This research aims to fill that gap by providing a detailed case study. Expected outcomes include a comprehensive assessment of PT X's ESG initiatives and their effectiveness, revealing their influence on reputation among stakeholders and identifying key perception drivers. Practical recommendations will be provided to optimize PT X's ESG strategy, enhancing its corporate reputation and sustainability. Ultimately, this research contributes empirical evidence regarding the relationship between ESG implementation and corporate reputation in Indonesia's mining industry, offering insights for companies in emerging economies on leveraging ESG practices for sustainable value